Intimate Connections: Marriage and mobilities across the modern Mediterranean and the Red Sea - Silvia Bruzzi (Cadernos de Estudos Africanos)
The prism of marriage can be a unique opportunity to write a social and cultural history in the modern Mediterranean and the Red Sea. The progressive dissolution of the Ottoman Empire, followed by the different settings of colonial encounters and/or the nation-building processes, led to the reform and reordering of multiple and contemporary marriages practices in a complex and dense imperial space such as the Mediterranean and the Red Sea regions. Legal regulations of marriage in the (post)Ottoman space are the results of superpositions, interactions and convergences of multiple juridical practices and norms, that included religious, customary, and civil regulations. Here, mobility played a crucial role in establishing and breaking new conjugal bonds, thus tracing the intimate entanglements between the Mediterranean and the Red Sea.